Devising a methodological approach to identifying the economic potential of production costs for eco-innovative products - Nesterenko, Iryna; Kashchena, Nataliia; Chmil, Hanna; Chumak, Oksana; Shtyk, Yuliia; Nesterenko, Oksana; Kovalevska, Nadiia (Eastern-European Journal of Enterprise Technologies, 2024)
The object of this study is the production costs of ecologically oriented innovative products. The problem under consideration was to improve the efficiency of cost management for the production of eco-innovative products by improving the methodical approach to identifying reserves for their reduction in order to ensure competitive advantages and strengthen the economic and environmental security of the enterprise. The devised methodological approach is based on a systematic analysis using economic and mathematical methods. It provides for the establishment of the dependence of costs per dollar of eco-innovative products on factors related to the economic potential of the enterprise, and the search for reserves for reducing costs for the production of eco-innovative products. The analysis technology was substantiated and modeling of costs per dollar of eco-innovative products of the enterprise was carried out using the principal component analysis. A distinctive feature of the built model was the consideration of the influence of micro-level factors, risk management, and the innovative component of the enterprise's economic potential. The resulting model is significant and reliable since the variation of costs per dollar of innovative products depends on the change in the principal components under investigation by 85 %. Within the framework of the devised methodical approach, a technology for calculating reserves for reducing production costs of enterprises producing eco-innovative products has been proposed. It was established that the potential of reducing costs per dollar of eco-innovative products for the totality of the investigated enterprises is on average 5.4 cents per dollar of costs. The area of practical use of the devised methodical approach is the process of minimizing and optimizing costs per hryvnia of eco-innovative products